Peran Kepemimpinan Transformasional terhadap Perilaku Kewargaan Organisasi Pada Guru Sekolah Menengah Atas - Nitya Goestiana Nafisah; Erika S. Kusumaputri (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2014)
The purpose of this study was to determine the correlation between transformational leadership and organizational citizenship behavior. The study involved 30 teachers (12 persons comingfrom SMA Muhammadiyah Kalasan and the remaining 18 arefrom high school UH Yogyakarta). Data was collected using organizational citizenship behavior scale and transformational leadership scale. Data analysis used the Pearson product moment. The result showed that there was no correlation between transformational leadership and organizational citizenship behavior among teacher (r = -0.274, p> 0.05).Keywords: Organizational Citizenship Behavior, Transformational Leadership